Postobturation Pain in Asymptomatic Non Vital Single Rooted Maxillary Teeth Following Single and Two Visit Root Canal Treatment (Chattagram Maa-O-Shishu Hospital Medical College Journal, 2016)
Objectives : The purpose of the present study was to asses the incidence and severity of pain after single and two visit Root Canal Treatment ( RCT ) / endodontic treatment in asymptomatic non vital single rooted maxillary teeth.Methods : Eighty one cases of endodontically involved asymptomatic, non vital, single rooted maxillary teeth without evidence of periapical radiolucency in radiograph were selected for this study. The patient were divided into two treatment group. In single visit group, all teeth were prepared and filled using the standardized preparation and lateral condensation filling technique. In the two visit treatment group, at the first appointment, the teeth were prepared and dressed with calcium hydroxide paste for 7 days. At the second appointment, the teeth were prepared and obturated by using lateral condensation technique. The frequency of post obturation pain was recorded as no pain, slight/ mild, moderate and severe pain and evaluated at the day 1 and at the day 7 after obturation. The data were analyzed statistically by using SPSS version 16. p-value